Preliminary Program. The 4th Scientific and Practical Conference "Moscow Transplantation" of the Interregional Public Organization "Society of Transplantologists" - Editorial Article (Трансплантология (Москва))
Preliminary Program. The 4th Scientific and Practical Conference "Moscow Transplantation" of the Interregional Public Organization "Society of Transplantologists".